2019
DOI: 10.9734/ejmp/2019/v30i130166
|View full text |Cite
|
Sign up to set email alerts
|

The Mitigating Effect of Jatropha curcas L. Latex against Genotoxicity Induced by Doxorubicin

Abstract: Jatropha curcas (Euphorbiaceae) is a multiple purpose lacticiferous plant with potential for biodiesel production and medicinal uses. There is in the literature different analyses about the toxic and cytogenotoxic effects of J. curcas extracts, but few information about latex toxicity. In addition, few models were employed to evaluate the toxicity response to J. curcas latex, and the toxicity in in vivo mammal’s model has not been tested yet. The cytotoxic, mutagenic and antimutagenic potential of J. curcas la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Studies using mouse bone marrow erythrocytes supported previous findings, which indicated that J.curcas latex can induce cytotoxic and mutagenic potential in mammalian cells ( Bailão et al., 2019 ). Surprisingly, co-administration of the latex along with doxorubicin, a common chemotherapy drug, reduced the normally-observed induced side effects.…”
Section: Anticancer Properties Of Latex-bearing Plant Extractssupporting
confidence: 82%
See 1 more Smart Citation
“…Studies using mouse bone marrow erythrocytes supported previous findings, which indicated that J.curcas latex can induce cytotoxic and mutagenic potential in mammalian cells ( Bailão et al., 2019 ). Surprisingly, co-administration of the latex along with doxorubicin, a common chemotherapy drug, reduced the normally-observed induced side effects.…”
Section: Anticancer Properties Of Latex-bearing Plant Extractssupporting
confidence: 82%
“…This is presumably due to J. curcas latex showing protective activity towards cells through scavenging free radicals. It is worth noting that since herb-drug interactions are not well inspected, such treatment can result in reduction of drug activity ( Bailão et al., 2019 ). To gain more data on the safety of J. curcas latex use, cytotoxicity of 37-10.000 μg/ml latex was evaluated by the MTT assay.…”
Section: Anticancer Properties Of Latex-bearing Plant Extractsmentioning
confidence: 99%